Biomimetic design and clinical application of Ti-6Al-4V lattice hemipelvis prosthesis for pelvic reconstruction - Zhuangzhuang Li; Yi Luo; Minxun Lu; Yitian Wang; Taojun Gong; Xuanhong He; Xin Hu; Jingjunjiao Long; Yong Zhou; Li Min; Chongqi Tu (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Objective This study aims to biomimetic design a new 3D-printed lattice hemipelvis prosthesis and evaluate its clinical efficiency for pelvic reconstruction following tumor resection, focusing on feasibility, osseointegration, and patient outcomes. Methods From May 2020 to October 2021, twelve patients with pelvic tumors underwent tumor resection and subsequently received 3D-printed lattice hemipelvis prostheses for pelvic reconstruction. The prosthesis was strategically incorporated with lattice structures and solid to optimize mechanical performance and osseointegration. The pore size and porosity were analyzed. Patient outcomes were assessed through a combination of clinical and radiological evaluations. Results Multiple pore sizes were observed in irregular porous structures, with a wide distribution range (approximately 300–900 μm). The average follow-up of 34.7 months, ranging 26 from to 43 months. One patient with Ewing sarcoma died of pulmonary metastasis 33 months after surgery while others were alive at the last follow-up. Postoperative radiographs showed that the prosthesis’s position was consistent with the preoperative planning. T-SMART images showed that the host bone was in close and tight contact with the prosthesis with no gaps at the interface. The average MSTS score was 21 at the last follow-up, ranging from 18 to 24. There was no complication requiring revision surgery or removal of the 3D-printed hemipelvis prosthesis, such as infection, screw breakage, and prosthesis loosening. Conclusion The newly designed 3D-printed lattice hemipelvis prosthesis created multiple pore sizes with a wide distribution range and resulted in good osteointegration and favorable limb function.